2018
DOI: 10.1371/journal.pone.0191595
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficacy of smear cytology and Robinson’s cytological grading of canine mammary tumors with respect to histopathology, cytomorphometry, metastases and overall survival

Abstract: Cytology is a simple, rapid, and inexpensive method used for pre-operative diagnosis of canine mammary tumors (CMTs) in veterinary practice. Studies related to human breast cancer showed the Robinson’s grading system—established for invasive ductal carcinoma, not otherwise specified (IDC, NOS) and used on cytological material—to not only closely correspond to the histopathological grading but also be helpful in assessing prognosis and selecting most suitable treatments before surgery. The objectives of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 48 publications
(103 reference statements)
1
39
1
3
Order By: Relevance
“…In this study, 84.61% of the samples analyzed had adequate cellularity, which corroborated the detection of malignant and/or benign features in cytology, and 90.9% had the diagnosis of tumor behavior compatible with histopathology. Dolka et al (2018) found correspondence between the two methods in 86.3%, which differed little from the data found in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this study, 84.61% of the samples analyzed had adequate cellularity, which corroborated the detection of malignant and/or benign features in cytology, and 90.9% had the diagnosis of tumor behavior compatible with histopathology. Dolka et al (2018) found correspondence between the two methods in 86.3%, which differed little from the data found in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Malignant neoplasias were more prevalent in this study, as well as in the study by Horta et al (2014) when evaluating 391 lesions, of which 56% were malignant neoplasias and 31% were benign neoplasias. Dolka et al (2018) analyzed 18 tumors and, of those, 75.3% were malignant and 24.7% benign. O diagnóstico de tumores malignos e benignos, neste estudo, foi levado em consideração devido ao baixo número amostral, porém considera-se relevante o desenvolvimento de outras pesquisas para avaliar as características de cada tipo histológico.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinic, a simple method to analyse and diagnose the mammary tumours in both human and animal is a cytological examination. However, this procedure is not satisfactory in canids because of the complex morphology of cells mammary tumours (Dolka et al, 2018). The histopathology and immunohistochemistry are known to be sufficient to analyse cells morphology and glycoprotein markers on the canine mammary tumours (Carvalho et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several Factors that may interfere and complicate the examination include: heterogeneous composition of tumors, incomplete clinical history, lack of standardization in the methodology, inter-observer variation, irregular distribution, cystic nature, small injuries, difficulties during the collection and presence of necrosis and inflammation [3] [4] [8]. As such, in about 5% to 15% of the cases, the Fine Needle Aspiration (FNA) biopsy did not reach a conclusive diagnosis, not because of the technique itself, but rather because of the inexperience of the pathologist or the characteristics of the injury [4] [8] [9]. Therefore, an alternative to increase quality in these cases is applying the ROSE (Rapid On-Site Evaluation) protocol, which consists in establishing standards to assure the sensitivity and specificity of the cytopathological exam without compromising its inherent quickness, considering all stages of the process, from requisition, collection, processing, reading and interpretation to issuing the diagnosis, as well as the determining of the previous classification of the injury [10].…”
Section: Introductionmentioning
confidence: 99%